Moderate Effects of Organizational Commitments on Team Commitments and Negotiations on Conflict Handling (Empirical Study: Indonesian Government) - Nurhamzah; Willy Abdillah; Fahruzzaman; Slamet Widodo (International Journal of Science and Society, 2022)
The conflict between teams is an interaction in the organization's daily life. To reveal the effect of negotiation and team commitment on conflict resolution (in integrating it) in the context of the construct of inter-team conflict and investigate how organizational commitment moderates the relationship between team negotiation and team commitment. The author conducted a questionnaire survey on employees in the Indonesian public sector with a sample of 224 responses. Structural equation modelling was used to analyze data and test hypotheses. Using Smart PLS 3.0. The results reveal that team commitment and negotiation positively relate to integrating behaviour. In addition, moderating organizational commitment to negotiation and team commitment was positively related to conflict handling behaviour when organizations have different orientations in their goals. Finally, higher conflict handling reinforces the positive effects of integrating negotiation and team commitment. The findings can help practitioners to predict team commitment, negotiation according to the organization and handling conflicts within the organization. This can allow practitioners to adjust their strategy and steer commitments and negotiations toward mutually beneficial conflict resolution outcomes. This study applies the theory of integrated conflict management due to team commitment and negotiation and empirically examines the relationship in the employee context. Moreover, this study reveals that organizational commitment moderates this linkage